2011
DOI: 10.1002/lary.21419
|View full text |Cite
|
Sign up to set email alerts
|

Nasoseptal “Rescue” flap: A novel modification of the nasoseptal flap technique for pituitary surgery

Abstract: Objectives: The introduction of the pedicled nasoseptal flap (NSF) has decreased postoperative cerebrospinal fluid (CSF) leak rates from >20% to <5% during expanded endoscopic skull base surgery. The NSF must be raised at the beginning of the operation to protect the posterior pedicle during the expanded sphenoidotomy. However, in most pituitary tumor cases, an intraoperative CSF leak is not expected but at times encountered. In these cases, a ''rescue'' flap approach can be used, which consists of partially h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
82
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 188 publications
(90 citation statements)
references
References 11 publications
1
82
0
1
Order By: Relevance
“…They suggested that this technique eliminates donor-site morbidity in patients with sellar tumors and no intraoperative CSF leak. 9 Kassam et al 10 reported that nasoseptal flap takedown and reuse for skull base reconstruction was a novel technique that optimized the ability of the endoscopic skull base surgeon to repair skull base defects reliably in revision procedures; the nasoseptal flap takedown had excellent success (95%) and minimal additional endonasal morbidity. Caicedo-Granados et al 11 introduced a reverse-rotation flap for reconstructing the donor site after a nasoseptal flap.…”
Section: Discussionmentioning
confidence: 98%
“…They suggested that this technique eliminates donor-site morbidity in patients with sellar tumors and no intraoperative CSF leak. 9 Kassam et al 10 reported that nasoseptal flap takedown and reuse for skull base reconstruction was a novel technique that optimized the ability of the endoscopic skull base surgeon to repair skull base defects reliably in revision procedures; the nasoseptal flap takedown had excellent success (95%) and minimal additional endonasal morbidity. Caicedo-Granados et al 11 introduced a reverse-rotation flap for reconstructing the donor site after a nasoseptal flap.…”
Section: Discussionmentioning
confidence: 98%
“…6 If a CSF leak is encountered or the resultant defect is larger than expected, the rescue flap can be fully harvested and used for reconstruction. In this case series, we report outcomes from the first cohort of patients who had a nasoseptal rescue flap raised prior to endoscopic pituitary surgery.…”
mentioning
confidence: 99%
“…Во время удаления опухоли СНЛПН располагается в носо-глотке. С целью сохранения пи-тающей ножки при транссфено-идальном доступе разработана методика «rescue flap» для ситуа-ций, когда в начале операции точно не известно, будет ли ис-пользован лоскут [16] Пластика медиальных и па-рамедианных дефектов пе-редних, средних и задних от-делов основания черепа при эндоназальном эндоскопиче-ском доступе и комбиниро-ванном («краниоэндоскопи-ческом») доступе [17] Ускорение заживления де- Кроме того, авторы выделяют дефекты содержимо-го глазницы (O). На основании этого подхода пред-ложен следующий алгоритм пластики: для рекон-струкции дефектов Ia или Ic, должен использовать-ся местный лоскут (надкостница свода черепа или височная мышца), при дефектах типа O или комби-нированных должен использоваться свободный ва-скуляризированный лоскут на питающей ножке.…”
Section: существующие алгоритмы пластики срединных дефектов передних unclassified